Attaining Workload Scalability and Strong Consistency for Replicated Databases with Hihooi - Georgiou, Michael A.; Panayiotou, Michael; Odysseos, Lambros; Paphitis, Aristodemos; Sirivianos, Michael; Herodotou, Herodotos (My University, 2021)
Database replication can be employed for scaling transactional workloads while maintaining strong consistency semantics. However, past approaches suffer from various issues such as limited scalability, performance versus consistency tradeoffs, and requirements for database or application modifications. Hihooi is a new replication-based master-slave middleware system that is able to overcome the aforementioned limitations. The novelty of Hihooi lies in its modern architecture as well as its replication and transaction routing algorithms. In particular, Hihooi replicates all write statements asynchronously and applies them in parallel at the replica nodes, while ensuring replica consistency. At the same time, a fine-grained transaction routing algorithm ensures that all read transactions are load balanced to the replicas consistently. This demonstration will showcase the key functionalities of Hihooi, including (i) practical management of system components and databases (e.g., add a new replica node), (ii) increased scalability compared to state-of-the-art approaches, and (iii) support for elasticity by suspending and resuming database replicas online without service interruption.
Keywords: Database replication; Transaction processing; Workload scalability; Concurrency control